2019
DOI: 10.21468/scipostphys.7.2.024
|View full text |Cite
|
Sign up to set email alerts
|

Entanglement in a fermion chain under continuous monitoring

Abstract: We study the entanglement entropy of the quantum trajectories of a free fermion chain under continuous monitoring of local occupation numbers. We propose a simple theory for entanglement entropy evolution from disentangled and highly excited initial states. It is based on generalized hydrodynamics and the quasiparticle pair approach to entanglement in integrable systems. We test several quantitative predictions of the theory against extensive numerics and find good agreement. In particular, the volume law enta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
225
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 297 publications
(239 citation statements)
references
References 85 publications
(173 reference statements)
13
225
1
Order By: Relevance
“…relaxation, dissipation, measurements) will also influence the entanglement dramatically. One notable example is, by introducing a continuous monitoring (damping) term in quench dynamics of free Fermion chain, it is found that the volume law entanglement is unstable under arbitrary weak damping if it is applied everywhere [33]. This is similar to the quantum Zeno effect [34], where the total system is measured continuously and localized near a trivial product state.…”
Section: Introductionmentioning
confidence: 99%
“…relaxation, dissipation, measurements) will also influence the entanglement dramatically. One notable example is, by introducing a continuous monitoring (damping) term in quench dynamics of free Fermion chain, it is found that the volume law entanglement is unstable under arbitrary weak damping if it is applied everywhere [33]. This is similar to the quantum Zeno effect [34], where the total system is measured continuously and localized near a trivial product state.…”
Section: Introductionmentioning
confidence: 99%
“…They, therefore, describe a much more versatile framework to model the influence of the environment on an open quantum system. The effect of POVM on entanglement evolution has been addressed for continuous measurements in free fermionic systems 31 , while the existence of an entanglement transition driven by measurement strength for interacting systems has been inferred by the study of mutual information 21 .…”
Section: Introductionmentioning
confidence: 99%
“…where Π j,j+1 is a graded permutation operator (9) and λ α are generalized chemical potentials. The case n B = n F = 1 gives the EKS model (a.k.a.…”
Section: Gl(nmentioning
confidence: 99%
“…The absence of a back action of the system onto its environment then facilitates a well defined mathematical description of open many-particle systems. In the quantum case this a priori results in a Markovian quantum stochastic many-particle system [6][7][8][9], which is however difficult to analyze. The customary approach in therefore to focus on the dynamics averaged over the environment, which leads to a description by the Lindblad master equation [10] for the time-dependent reduced density matrix ρ(t)…”
Section: Introductionmentioning
confidence: 99%